2021
DOI: 10.31584/jhsmr.2021798
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cancer Patients Requiring Palliative Care in Outpatient Clinics in a Tertiary Hospital in Southern Thailand

Abstract: Objective: To estimate the prevalence of patients requiring palliative care in outpatient clinics and associated factors.Materials and Methods: A cross-sectional study was conducted by retrospectively reviewing the electronic medical records of cancer patients visiting the outpatient clinics in the major tertiary care institution in southern Thailand during 1 January– 31 December 2018 from the Hospital Information System. The Supportive and Palliative Care Indicators Tool in Low Income Settings (SPICT-LISTM) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The result of the study is in line with the study done in Thailand. 23 This might be due to multiple medical conditions elderly people face such as chronic disease and different musculoskeletal diseases. 25 , 26 The results of the study also showed that male patients had a significantly higher requirement for palliative care compared to female patients, which was five times that of their counterpart (AOR=5.31, 95% CI=1.68–11.79).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The result of the study is in line with the study done in Thailand. 23 This might be due to multiple medical conditions elderly people face such as chronic disease and different musculoskeletal diseases. 25 , 26 The results of the study also showed that male patients had a significantly higher requirement for palliative care compared to female patients, which was five times that of their counterpart (AOR=5.31, 95% CI=1.68–11.79).…”
Section: Discussionmentioning
confidence: 99%
“…But this result is different from the study done in Thailand that showed malignant neoplasms of bone and articular cartilage required higher palliative care than other types of cancer. 23 This difference might be due to the different types of cancers found at the Saint Paul hospital. The reason nasopharyngeal cancer needs palliative care more than other types of cancer might be due to its impact on breathing, speaking, and hearing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tool has been translated into more than eight languages including Spanish (SPICT-ES™) 17 , Italian (SPICT-IT™) 19 , German (SPICT-DE™) 32 and Japanese (SPICT-J™) 20 although not all versions have been formally validated. [25][26][27]33 Furthermore, there is evidence to suggest that the SPICT™ may facilitate changes in the goals of care and documentation of end of life care planning and patient wishes. Incidentally the SPICT™ appears to be positively received by clinicians with some suggesting that the tool provides a common language for clinicians when collaborating to identify palliative care needs and provide palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, the SPICT-LIS was translated into Thai, with cross-cultural validation by Sripaew et al and subsequently tested using real-world data in a retrospective study by Fumaneeshoat et al [ 7 ] using the Thai-translated SPICT-LIS to identify cancer patients who may have benefited from palliative care in Thailand. They found that 7.8% of 9,990 patients with cancer might have qualified for palliative care [ 8 ]. However, it is challenging to evaluate all cancer patients using an instrument such as the SPICT-LIS to evaluate which patients would benefit from palliative care in real life due to limited resources, healthcare providers, and knowledge.…”
Section: Introductionmentioning
confidence: 99%